Radiological and Bronchoscopic Findings for the Better Yield of Tissue Diagnosis in Lung Malignancy - Khunjeli, Rabindra; Shrestha, Sanjeet Krishna; Karki, Manan; Srivastava, Brajendra; Mohsin, Ushab Rana (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: In flexible bronchoscopy, absence of endobronchial abnormality blinds the bronchoscopist towards the location of the lung lesion. Guided techniques for bronchoscopy are not available in Nepal. Hence, diagnostic yield is very low. There is need to find the factors to improve yield. This study evaluates the radiological and bronchoscopic findings that can help in histo-pathological yield.Methods: This retrospective study included 557 bronchoscopies done for the evaluation of lung malignancy. Radiological, bronchoscopic and histo-pathological abnormalities were classified and evaluated. The study aimed at finding the radiological and bronchoscopic factors commonly associated with positive yield in histopathology.Results: Among 557 subjects, 490 had abnormal chest X-ray. Mass lesion was seen in 252(45.24%), cavity in 19(3.41%), collapse in 93(16.69%), consolidation in 81(14.54%), pleural effusion in 28(5.02%) and fibrosis in 17(3.05%) subjects. Total of 314(56.37%) abnormal bronchoscopies included: endobronchial growth 200(35.9%), narrowing 66(11.84%), obstruction 107(19.27%) and ulcer 16(2.8%). Histopathology was positive in 198(35.54%) including 179 (32.13%) lung malignancies. The diagnostic yield for getting positive histopathology for the study population was 35.54%, for mass lesion was 40.47% and for abnormal bronchoscopy was 54.78%. Significant correlation was identified among mass lesion, endobronchial abnormality and positive histo-pathology. Central mass lesion, collapse and consolidation showed significant association with lung malignancy. Significant association was also identified between histo-pathology and endobronchial growth, obstruction and ulcer. Conclusions: The diagnostic yield increases with positive endobronchial abnormality. Presence of central lung lesion, collapse and consolidation favour positive yield of histo-pathology. Endobronchial growth, obstruction and ulcer are likely to yield malignant histopathology reports.